2022
DOI: 10.5334/aogh.3496
|View full text |Cite
|
Sign up to set email alerts
|

Maternity Waiting Home Interventions as a Strategy for Improving Birth Outcomes: A Scoping Review and Meta-Analysis

Abstract: Background and Objective: Over 300 000 women worldwide die due to pregnancy-related complications annually, with most occurring in developing countries where access to skilled obstetric care is limited. Maternity waiting homes (MWHs) are one intervention designed to increase access to skilled prenatal care in resource-limited settings. MWHs are defined as accommodations at or near a health facility where pregnant women can stay in the final weeks of their pregnancy so they can be easily transferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…13 In the meta-analysis by Smith et al in 2022, MWHs have a protective effect on maternal and perinatal mortality but fail to reduce the rate of Cesarean sections. 14 MWH users and non-users suffered no maternal or perinatal mortality in this study because Korea has a relatively better medical healthcare system than other low-income countries and because there was a small data sample.…”
Section: Discussionmentioning
confidence: 94%
“…13 In the meta-analysis by Smith et al in 2022, MWHs have a protective effect on maternal and perinatal mortality but fail to reduce the rate of Cesarean sections. 14 MWH users and non-users suffered no maternal or perinatal mortality in this study because Korea has a relatively better medical healthcare system than other low-income countries and because there was a small data sample.…”
Section: Discussionmentioning
confidence: 94%
“…33 It has been widely proven that collaboration between stakeholders is the key to utilizing MHWs to reduce maternal mortality rates. 15,17,24 Collaboration can be conducted with interdisciplinary health and non-health stakeholders. 25 The WHO revealed that strengthening collaboration among multilateral organizations can be done to accelerate each country's progress toward health-related Sustainable Development Goals.…”
Section: Discussionmentioning
confidence: 99%
“…Maternity Waiting Homes (MWHs) is an intervention method that aims to aid pregnant women to be closer to delivery facility services. 15 MWHs facilitate pregnant women to stay in a house in their last weeks of pregnancy so that they can be easily transferred to a health facility for delivery with health professionals and receive prompt emergency obstetric care when needed. 15,16 MWHs have been proven to reduce maternal mortality by 80% in developing countries.…”
Section: Mmr Inmentioning
confidence: 99%
See 1 more Smart Citation
“…While recent systematic reviews and meta-analyses report limited, mixed and inconclusive evidence regarding MWH effectiveness,5 7 8 individual studies have associated the MWH-facility birth intervention with increased odds of facility birth9–11; decreased maternal and perinatal mortality12 13; reduced risk of low birth weight14; and increased odds of attendance at all recommended postnatal visits within 6 weeks of birth 15. The intervention remains under-utilised in LMICs,16 which suggests a mismatch between one or more aspects of the implemented MWH-facility birth model and the capacities, expectations, experiences, needs and preferences of its intended beneficiaries.…”
Section: Introductionmentioning
confidence: 99%